PTU-124 The Association of the Joint Hypermobility Syndrome with Functional Gastrointestinal Disorders – an Interesting New finding that may Explain Aetiology. (4th June 2013) - Fikree, A; Aktar, R; Gillespie, K V; Glasgow, L E; Morris, J K; Farmer, A; Grahame, R; Knowles, C H; Aziz, Q
Abstract : Introduction: Functional Gastrointestinal Disorders (FGID) are common, but their cause is unknown. Joint hypermobility syndrome (JHS) is a common non-inflammatory connective tissue disorder characterised by joint hyperflexibility. It is associated with gastrointestinal (GI) symptoms (1), in particular unexplained symptoms (2). The association between JHS and FGID has never been studied. Methods: A nested case control study in patients aged 18–70 attending secondary care was performed. 694 consecutive new referrals to GI clinics were assessed for JHS using the Brighton criteria, prior to their outpatient consultation. Subsequent investigation by their gastroenterologist led to a diagnosis that was functional, organic or gastrooesophageal reflux (GOR); the latter were excluded due to the mixed aetiology of reflux. The control group consisted of 92 patients referred to secondary care for non-GI symptoms-those with diabetes, pregnancy, neuromuscular disorders or inflammatory arthritis were excluded. Controls were similarly assessed for JHS. JHS prevalence was compared in patients with FGID, organic GI disorders, and controls. Results: Of the 694 GI patients, 26 had GOR and 52 had not received a diagnosis–these were excluded. Thus 616 GI patients were included in the study: 363 had FGID, 253 had organic disorders. There were no significant age or gender differences between FGID and controls (age: 40.3 ± 0.69 vs 42.7 ± 1.5; 64% vs 67% females). Compared to FGID patients, organic patients were older (43.9 ± 0.92 vs 40.3 ± 0.69, p:0.002) and less likely to be female (54% vs 64%, p:0.008).The prevalence of JHS in FGID patients in secondary care was 40.5%. This was significantly higher than in organic GI patients (26.9%, p:0.000) and in controls (25%, p:0.006). Even after adjusting for age and gender differences, JHS was significantly associated with FGID (p:0.005). Conclusion: This is the first study that demonstrates a strong association between JHS and FGID, as compared to both organic GI and non-GI conditions. This suggests a potential connective tissue aetiology for 40% of FGID patients in secondary care. Furthermore, the high prevalence of JHS in FGID suggests that this common diagnosis is often overlooked. Our results have implications for future FGID research and efforts must now be focused to determine the mechanism of symptoms and identification of appropriate treatments for this subgroup of patients. Disclosure of Interest: None Declared References: Castori, M., et al., Am J Med Genet A, 2010. 152A (3): p. 556–64. Zarate, N., et al., Neurogastroenterol Motil, 2010. 22 (3):252-e78.